Penerapan Media Audio Visual dalam Meningkatkan Konsentrasi Belajar Siswa pada Pembelajaran PAI Kelas IX E di SMP Negeri 4 Kebumen - Ahmad Rozik Al Hasan; Jihad Fatkhurohim; Ratu Shyfa; Siti Fatimah; Imam Subarkah (IAINU Kebumen, 2023)
This study aims to determine the increase in the concentrantion of students in participating in Islamic Religious Education Learning at SMP Negeri 4 Kebumen. this research is a classroom action research that was carried out for two meetings in easch cycle. Each cycle consists of the stages of planning, implementing, abserving, and reflecting. The research subjects in this study ware grade IX e students of SMP Negeri 4 Kebumen. data collection techniques using tests, observations, and interviews. Data validity using triangulation. The results of the analysis show that learning in the first cycle as much as 57% of the children have concentrated on learning Islamic Religious Education. Whereas in cycle II as many as 82% of the children had concentrated on participating in Islamic Religious Education Learning. So it can be concluded that there is an increase in student concentration in learning Islamic Religious Education through the application of audio-visual media.